Semantic changes of lexemes σώφρων, σωφροσύνη and their cognates in Ancient Greek (From Homer to New Testament) - Левко, Олександр Вадимович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article analyses the semantic evolution of lexemes σώφρων, σωφροσύνη and their cognates in Ancient Greek language with particular focus on contrastive investigation of their contextual meanings in New Testament and classic Greek texts. These lexemes and their derivatives belong to lexemes, which cause difficulties in attempts of their appropriate translation because of the breadth of their meanings and the semantic evolution from the poems of Homer to the ascetic treatises of the Byzantine age. Despite the fact that the concept σωφροσύνη occupies an important place in the system of both Ancient and Christian values, its exact correspondences in modern languages are difficult to find. For nearly a thousand years history of usage the semantics of σωφροσύνη has extended from etymologically determined and prototypical meaning "soundness of mind" to "prudence", "modesty", "obedience", "temperance", "self-restraint", "control of pleasures and desires" in Classic age of VI-IV centuries B.C. and "chastity", "innocence", "virginity" in Early Christian epoch. It is also revealed that traditional Christian interpretation of σωφροσύνη as chastity and virginity was formed only in Patristic discourse, whereas the use of this value term in New Testament is still linked with its prototypical meanings in Ancient Greek texts of the Classic age. It is noted that meanings of σωφροσύνη vary according to their attribution to different corresponding groups such as men, women, girls, boys, citizens and state. This tendency to polysemy is fully observed in Classic Greek non-philosophical texts, although gender difference in semantics of σώφρων and σωφροσύνη is still present in the New Testament Greek.